The importance of the dimensions of a smart city – a survey in small cities - Lopes, Isabel Maria (2018)
The pursuit of territorial rebalance through an investment in new development models for cities is adapting them to the new challenges (from demographic to environmental) and with a duty to turn them into smart cities without taking away their identity. However, the definition of smart cities and the measurement of their levels of sustainability, quality of life and wellbeing are still low-consensus topics, and so are the dimensions and sub-dimensions which should have most weight when classifying a city as a “smart city”. In this research work and by means of a survey, we intend to assess, as far as possible, which dimensions (Governance, Innovation, Sustainability, Inclusion and Connectivity) are seen as the most important for a city to be considered a smart city. The results are discussed in the light of literature and future works are identified with the aim to shed some light into such an emerging, promising and current field as this one of “smart cities”.